Águas da região do delta do Rio Doce com ênfase no vale do Suruaca, Linhares-ES - Lani, João Luiz; De Rezende, Servulo Batista; Sartain, Jerry D.; Lani, José Antônio (Geografares, 2009)
DOI: 10.7147/GEO7.157